Plumularioid hydroids (Cnidaria: Hydrozoa) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program - Galea, Horia R.; Maggioni, Davide (European Journal of Taxonomy, 2020)
This study reports on 25 species of hydroids occurring in the collections gathered during KANACONO and KANADEEP expeditions carried out in the SE of New Caledonia in 2016, and off the western coast of the island in 2017, respectively. Of these, 19 have not been dealt with in earlier reports on these collections. Two new genera and four new species are described, viz, Actinopluma mirifica Galea gen. et sp. nov., provisionally assigned to the family Kirchenpaueriidae Stechow, 1921, Schizoplumularia helicoidalis sp. nov., belonging to the Plumulariidae McCrady, 1859, and Corhiza patula Galea sp. nov. and Thamnopteros uniserius Galea gen. et sp. nov., both placed in the family Halopterididae Millard, 1962. The gonotheca and the medusoid gonophore of Plumularia contraria Ansín Agís et al., 2014 are described for the first time, allowing a genus transfer to Dentitheca Stechow, 1919, as D. contraria comb. nov. Plumularia conjuncta Billard, 1913, known earlier from a minute portion of colony, is redescribed based on a complete, though infertile, specimen. Similarly, complete specimens corresponding to the hydroid previously referred to as Antennella megatheca Ansín Agís et al., 2009 are documented, allowing a provisional reallocation to Corhiza Millard, 1962 and a description of its so far unknown gonothecae. Fertile material assignable to the poorly-known Monostaechas fisheri Nutting, 1905 allows the recognition of this hydroid as a valid species, distinct from M. quadridens (McCrady, 1859). Most taxa are illustrated to validate the reliability of their identifications. Finally, phylogenetic reconstructions of the families Aglaopheniidae, Plumulariidae, and Halopterididae, based on the 16S rRNA, allowed a first genetic characterization of some of the species dealt with in this work.